The effect of treatment modifications by an onco-geriatric MDT on one-year mortality, days spent at home and postoperative complications. Issue 5 (June 2021) - Festen, Suzanne; van der Wal-Huisman, Hanneke; van der Leest, Annya H.D.; Reyners, Anna K.L.; de Bock, Geertruida H.; de Graeff, Pauline; van Leeuwen, Barbara L.
Abstract: Objectives: Decision-making in older patients with cancer can be complex, as benefits of treatment should be weighed against possible side-effects and life-expectancy. A novel care pathway was set up incorporating geriatric assessment into treatment decision-making for older cancer patients. Treatment decisions could be modified following discussion in an onco-geriatric multidisciplinary team (MDT). We assessed the effect of treatment modifications on outcomes. Materials and methods: This retrospective study was performed in the surgical department of a University Hospital. Patients of 70 years and older with a solid malignancy were included. All patients underwent a nurse-led geriatric assessment (GA) and were discussed in an onco-geriatric MDT. This could result in a modified or an unchanged treatment advice compared to the regular tumor board. Primary outcome was one-year mortality. Secondary outcomes were post-operative complications and days spent in hospital in the first year after inclusion. Results: For the 184 patients in the analyses, the median age was 77.5 years and 41.8% were female. For 46 patients (25%), the treatment advice was modified by the onco-geriatric MDT. There was no significant difference in one-year mortality between the unchanged and modified group (29.7% versus 26.1%, p  = 0.7). There were, however, significantly fewer days spent in hospital (median 5 vs 8.5 days p  = 0.02) and fewer grade II or higher postoperative complications (13.3% versus 35.5% p  = 0.005) in the modified group. Conclusion: Incorporating geriatric assessment in decision-making did not lead to excess one-year mortality, but did result in fewer complications and days spent in hospital. Highlights: Incorporating geriatric assessment led to a modified treatment advice in 25% of patients. Modifications were mostly toward less intensive treatment. Follow-up revealed no excess one-year mortality compared to patients with an unchanged advice. The modified group experienced less complications and less days spent in hospital.